The Development of Skin Analyser for Skin Type and Skin Problem Detection - Juwanda, Fatin Syuhada; Mat Zin, Harnani (Journal of ICT in Education, 2021)
The skin is the body’s largest organ and it is essential to take good care of it. Various skincare products are existing in the market that can be used. However, the wrong selection of ingredients can cause irritation and skin sensitivity that would lead to low self-esteem. Moreover, there is a lack of a platform that provides the user with knowledge regarding skin and skincare ingredients. Thus, this study aims to develop a mobile application that can analyse the face skin type. In this study, automatic face skin detection is proposed. This mobile application gives a recommendation of ingredients based on the user’s skin type. The prototyping model was used as a methodology together with Android Studio as the software tool and JavaScript as the programming language. The usability testing involved 30 respondents and the results show positive feedback towards the features and functionalities of the proposed mobile application. Thus, the development of this Skin Analyser mobile application can help many young women to check on their skin and help them feel more confident.